130k views
0 votes
Y = -6x+5 -2x + y =5

User Frenus
by
4.9k points

1 Answer

2 votes

Answer:

Y=18x

Explanation:

You have to add 6x plus 5 and you get 11x then you have to subtract 2x from that 11x to get 9x then you have to add 4 plus 5 and you get 9 and add 9x +9 and you get 18x. So Y=18x

If i am wrong i am sorry i am just trying to help but tell me whether i am right or wrong.

User Krakover
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.